2023
DOI: 10.3390/jfb14050287
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coatings of Dental Implants: A Review

Abstract: Replacement of missing teeth is possible using biocompatible devices such as endosseous implants. This study aims to analyze and recognize the best characteristics of different implant surfaces that ensure good peri-implant tissue healing and thus clinical success over time. The present review was performed on the recent literature concerning endosseous implants made of titanium, a material most frequently used because of its mechanical, physical, and chemical characteristics. Thanks to its low bioactivity, ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 102 publications
0
7
0
1
Order By: Relevance
“…They concluded that rough surfaces and load implants resulted in higher values of every parameter studied. Another recent review that aimed to analyze different implant surfaces and try to identify the ideal structure from a clinical and durability point of view [52] concluded that treated surfaces allowed better osseointegration and better cell proliferation, as long as a better propensity for epithelial cell adhesion and attachment, proliferation, and differentiation of osteoblastic cells. They also suggest that 3D printed implants deserve further investigation to help improve biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that rough surfaces and load implants resulted in higher values of every parameter studied. Another recent review that aimed to analyze different implant surfaces and try to identify the ideal structure from a clinical and durability point of view [52] concluded that treated surfaces allowed better osseointegration and better cell proliferation, as long as a better propensity for epithelial cell adhesion and attachment, proliferation, and differentiation of osteoblastic cells. They also suggest that 3D printed implants deserve further investigation to help improve biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The dental implant coating process comprises six primary techniques: Plasma spraying, nanospray drying, sol-gel, hydrothermal, self-assembly, and 3D printing [13]. Currently, a range of compounds are used to coat dental implants, including polyhydroxyalkanoates, calcium phosphate, carbon, bisphosphonates, hydroxyapatite (HA), bone-stimulating chemicals, bioactive glass, bioactive ceramics, collagen, and chitosan [56]. Among these particles, HA is one of the popular bioceramic substances often used as a coating material.…”
Section: Additive Techniquesmentioning
confidence: 99%
“…Змочуваність і поверхнева енергія -ключові параметри при адгезії та поширенні остеобластних клітин [18]. Грубозернисту поверхню з піскоструминною обробкою і протравленням кислотою (SLA), завдяки гідрофільності, використовують для найновіших комерційних зубних імплантатів [19]. У великому сімействі поверхонь типу SLA розрізняють три підгрупи.…”
Section: обговоренняunclassified